Komunitas ASEAN: Penyelesaian Sengketa dan Penegakkan Hukum - Lestari, Hesty D. (Indonesian Journal of International Law, 2008)
ASEAN will turn to an ASEAN Community by 2015. The ASEAN Community shall consist of three pillars, namely political and security cooperation, economic cooperation, and socio-cultural cooperation. It aims to deepen the ASEAN integration and to ensure durable peace, stability, and shared prosperity in the region. The ASEAN Community will also have its own legal order, which should be implemented by its member states.